Nature and Properties of Some Introouced Teak (Tectona grandis) Growing Soils of North-west Bengal - Gangopadhyay, S. K.; Nath, S.; Banerjee, S. K. (Indian Forester, 1987)
Nature and properties of some introduced teak (Tectona grandis) growing solis of Nort-west Bengal were studied in order to evaluate the characteristics of the solis supporting the species. It was found that since teak was growing well in the area, the characteristics and nature of the solis must be favourable for the growth and development of the species. Information from other good teak growing areas will help to generalise the range of the characteristics of the soils suitable for the species.